Social Protection Without Borders: Latin American Challenges in the Reform of the International Financial Architecture - Serafini Geoghegan, Verónica (Sociedad y Economía, 2025)
IntroductionAmid the multiple crises the world is currently facing, an increase in migration linked to global care chains– largely led by women–is expected. In this context, it becomes urgent to debate the implementation and financing of transnational social protection policies.ObjectiveThis article proposes an integrated approach to the implementation of transnational social protection policies, in parallel with the reform of the international financial architecture, in order to create the fiscal space required to finance such policies.MethodologyThe article is based on a literature review of ongoing international debates and agreements.ResultsGlobal care chains have enabled high-income countries to reduce the costs associated with social reproduction and care work, without ensuring job quality or social protection, either during working life or in retirement. The reform of the international financial architecture, in terms of both international taxation and debt, aims to expand fiscal space.ConclusionsFrom an ethics of care perspective and in line with the universal principles of human rights, this study argues for a collective and global responsibility in the distribution of the costs of social reproduction and care. Therefore, current debates must be able to integrate both processes—the design and implementation of transnational social protection policies and the reform of the international financial architecture—highlighting their interdependencies and the need for coordinated approaches from a feminist and Latin American perspective.